From postfeminist discourse to postfeminist sexism: The case of duckface photos - Λιότζης, Ευάγγελος (The Greek Review of Social Research, 2016)
Postfeminism, as a distinct cultural phenomenon, has been and continues to be a controversial issue both within the scientific and feminist thought, and in public debate in general. The duckface photos, as a concretely structured type of images, are a typical example of the reproduction of postfeminist discourse in the modern communication environment. Through this case, there is an effort to determine the contribution of postfeminist aesthetics in the reproduction of a “postfeminist oriented sexism”.